Model Pengembangan Industri Batako Ramah Lingkungan di Kota Makassar - Nurlita Pertiwi; Mithen Lullulangi (Seminar Nasional LP2M UNM, 2021)
Abstract. This research is an experimental test on concrete bricks with waste as additives and cement substitution materials. The waste material used is rice husk ash as a waste product of agricultural activities and brick fragments as waste in the construction industry. The design of concrete brick is formed by a material with the composition 1PC: 5 Sand: 0.5 water. Meanwhile, the proportion of additional waste is 0.5%, 1%, and 1.5% to the weight of cement. The results showed that the additive method produced better quality bricks than the substitution method. The test results also show that the addition of waste makes bricks suitable for construction in walls without external loads.Keywords: Compressive strength, Absorption, Rice Husk Ash